Cyclical Behavior of Inventories and Growth Projections Recent Evidence From Europe and the United States - Hoffmaister, Willy (IMF Working Papers; Working Paper ;, 2010)
In the United States and a few European countries, inventory behavior is mainly the outcome of demand shocks: a standard buffer-stock model best characterizes these economies. But most European countries are described by a modified buffer-stock model where supply shocks dominate. In contrast to the United States, inventories boost growth with a one-year lag in Europe. Moreover, inventories provide limited information to improve growth forecasts particularly when a modified buffer-stock model characterizes inventory behavior.